Identidade acadêmica em artigos científicos: uma análise comparativa da construção das vozes autorais por alunos de graduação. - Morais, Lídya Rafaella da Silva (2022)
Throughout their trajectory in an undergraduate course, students feel the need to build a social identity that is compatible with their academic community. Their teachers tend to raise expectations about how they should behave when faced with the different genres that are part of the literacy events that are typical of this environment. Thus, we proposed a comparative research on the relationship between the forms of expression of the authorial voice in texts and the construction of academic identity by undergraduate students. For this purpose, we used a corpus composed of 20 scientific articles divided into two groups of students, the first one consists of 10 articles written by Letters undergraduates from the Catholic University of Pernambuco (UNICAP), and the second one of 10 articles written by Letters undergraduates from different Brazilian universities that were published in the Journal Ao Pé da Letra, created by the Federal University of Pernambuco (UFPE), which may have more than one authorship. Methodologically, we relied on the integrative proposal of Castelló et al. (2011) that addresses the manifestation of voice in texts using a system composed of three dimensions of analysis to be used in the study of the construction of draft and finalized texts, which integrates intertextuality in the forms of citation and allusion proposed by the authors, the discursive resources of positioning presented by Hyland (2005a), and the rhetorical movements pointed out by Swales (1990). Our objective with this work was to comparatively analyze the forms of expression of the authorial voice in these two groups of texts, taking them as strategies adopted in the construction of academic identity. The results suggest that, in unpublished texts, the voice tends to be less intense and categorical than in published texts, being less emphatic in its placements, while in effectively published texts there is the presence of a more assertive voice that demonstrates a greater degree of confidence in their statements, investing in arguments that claim an academic identity of their own. Thus, the two groups analyzed presented more similarities than differences, differing only in some aspects that reflect the final purposes of their work, expressing a voice that characterizes the authors, and showing that the students are capable of producing academic texts, but, at the same time, they are still building their identities.